Changes in running mechanics and spring–mass behavior induced by a mountain ultra-marathon race - Morin, J.B.; Tomazin, K.; Edouard, P.; Millet, G.Y. (Journal of biomechanics, 2011)
Changes in running mechanics and spring–mass behavior due to fatigue induced by a mountain ultra-marathon race (MUM, 166km, total positive and negative elevation of 9500m) were studied in 18 ultra-marathon runners. Mechanical measurements were undertaken pre- and 3h post-MUM at 12kmh−1 on a 7m long pressure walkway: contact (tc), aerial (ta) times, step frequency (f), and running velocity (v) were sampled and averaged over 5–8 steps. From these variables, spring–mass parameters of peak vertical ground reaction force (Fmax), vertical downward displacement of the center of mass (Δz), leg length change (ΔL), vertical (kvert) and leg (kleg) stiffness were computed. After the MUM, there was a significant increase in f (5.9±5.5%; P<0.001) associated with reduced ta (−18.5±17.4%; P<0.001) with no change in tc, and a significant decrease in both Δz and Fmax (−11.6±10.5 and −6.3±7.3%, respectively; P<0.001). kvert increased by 5.6±11.7% (P=0.053), and kleg remained unchanged. These results show that 3h post-MUM, subjects ran with a reduced vertical oscillation of their spring–mass system. This is consistent with (i) previous studies concerning muscular structure/function impairment in running and (ii) the hypothesis that these changes in the running pattern could be associated with lower overall impact (especially during the braking phase) supported by the locomotor system at each step, potentially leading to reduced pain during running.